Verification of probability density evolution method through shaking table tests of a randomly base-driven structure. Issue 3 (February 2018) - Mei, Zhen; Guo, Zixiong
Over the last decade, a family of probability density evolution method for analysis of general stochastic dynamical systems has been developed. A large number of numerical examples indicate that this method has advantages in quantification of stochastic dynamic response, in assessment of global reliability and in stochastic optimal control of structures, while its experimental verification is still lacking. The main purpose of this article, with the consequence, is to experimentally investigate the accuracy and efficiency of the probability density evolution method through shaking table tests of a randomly base-driven structure. Analytical results demonstrate that the probability density evolution method is capable of evaluating the probability information, including the mean, the standard deviation, the instantaneous probability density function and its evolution, of structural responses exactly. Furthermore, stochastic response analyses of the tested structure without dampers subjected to three different sets of ground motions are conducted to validate the correctness and reliability of the probability density evolution method. It is concluded that a small amount of representative samples is able to accommodate a relatively accurate analytical result of stochastic dynamical systems, indicating a significant efficiency of the probability density evolution method.